Evaluation of energy efficiency of solar roofing using mathematical and experimental research - Mysak, Yosyf; Pona, Ostap; Shapoval, Stepan; Kuznetsova, Marta; Kovalenko, Tetiana (Eastern-European Journal of Enterprise Technologies, 2017)
A relevant issue today is the principle of energy efficiency and rational use of energy resources. At present, solar heating systems with conventional solar collectors are quite expensive. Given this, we designed and patented a solar roofing, which combines the functions of a solar collector and a metal corrugated part of the pitched roof. The feature of solar roofing is that its heat absorber is made of the corrugated roofing material of the building. This makes it possible to significantly reduce the cost of the solar system, improve its strength and simplify the design. Comprehensive solution of the issues of fixing solar collectors directly to the elements of the roof has broad prospects because, in this case, the possibility of replacing a part of the roof with them can be implemented. This eliminates additional load on the carrying structures and reduces the cost of solar heating in general. We developed a mathematical model of the work of a solar roofing in the heating system, which is a dependence of calculation of heating temperature of the heat carrier in the tank-accumulator on intensity of the heat flow and period of radiation. It was established that at changing incident angles of the heat flow from 90º to 30º, effectiveness of solar roofing reduces insignificantly compared with the flat solar collectors. We improved dependences of change in the efficiency of solar heating systems using a solar roofing on the direction and velocity of the air flow. It is established that energy efficiency of a solar roofing is larger affected by velocity of air flow, while its direction is less important.